A study of serum ferritin levels among voluntary blood donors - G., Deepa Devi; P., Arumugam; Hamsavardhini, Swathandhran; S. T., Radhiga (International Journal of Research in Medical Sciences, 2017)
Background: The frequent blood donations may lead on to iron deficiency and iron deficiency anaemia. Estimation of haemoglobin and hematocrit levels alone in voluntary blood donors may not be adequate. Hence this study was taken to estimate the serum ferritin level among voluntary blood donors with different frequency of donation and compare with hemoglobin levels. Methods: A Cross sectional study consisted of 314 voluntary blood donors, they were grouped into control groups donating blood for the first time and group donating blood once, twice and thrice in a year. The red cell parameters were measured by automatic cell count analyzer and estimation of serum ferritin by ELISA method. Results: There were 88.2% males and 11.8% females. The distribution of donors on the basis of the frequency of donation per year were 50% first time, 23.9% once a year, 19.7% twice a year and 6.4% thrice a year donation. A statistically significant correlation was seen between frequency of donation and total number of life time donations and serum ferritin levels. Distribution on the basis of number of donations per year and serum ferritin <15 ng/ml in male donors were 6.9 % in first time, 19.4 % in once a year, 26.7% in twice a year and 50% in thrice year donation. Among female donors 40.7% in first time, 50% in once a year, 50% in twice a year donation had serum ferritin levels <15 ng/ml. Conclusions: In this study, there was a definite correlation between dwindling of serum Ferritin level and the frequency of donation. As a part of donor haemovigilance program, our study suggests estimation of serum ferritin level, iron supplementation and donor health education on balanced nutritious diet for at least female donors and regular male donors to maintain adequate donor pool.